Low‐Intensity Precipitation Dominates Peninsular Spain (1961–2022) - Ahmed M. El Kenawy; Santiago Beguería; Fernando Domínguez‐Castro; Amar Halifa‐Marín; Maria Adell‐Michavila; Borja Latorre; Magí Franquesa; Islam M. Gaber; Islam M. Hamdi; Sergio M. Vicente‐Serrano (International Journal of Climatology, 2026)
Precipitation regimes across peninsular Spain have undergone a structural reorganisation toward low‐intensity dominance over the past six decades (1961–2022), driven by redistribution across intensity classes rather than monotonic changes in totals. These findings are derived from a dense observational network of 2096 rain gauges. Rather than focusing solely on precipitation totals or extremes, we introduce a redistribution‐based diagnostic framework that jointly evaluates precipitation frequency (RF) and volumetric contribution (RC) across the full intensity spectrum (P1–P99). Results reveal that the lowest percentiles (P1–P10) show widespread positive trends in both RF and RC, with up to ~60% of the territory exhibiting statistically significant increases, particularly during winter and fall ( p

Non‐Stationary Dry‐Spell Hazard Probabilities for Spain - S. M. Vicente‐Serrano; S. Beguería; A. Royo; A. El Kenawy; M. Franquesa; A. Halifa‐Marin; M. Adell‐Michavila; A. Crespillo; D. Pérez‐Pajuelo; F. Domínguez‐Castro; C. Azorin‐Molina; L. Gimeno; et al. (International Journal of Climatology, 2026)
This study provides a comprehensive assessment of long‐term changes in dry‐spell dynamics across Spain for the period 1961–2024, using both classical non‐parametric methods and a novel non‐stationary probabilistic framework applied to exceedance series of dry‐spell durations. Using daily precipitation data from a dense network of quality‐controlled stations, dry‐spells were identified based on four thresholds (0.1, 1, 5, and 10 mm) to characterize their duration statistics, and generalized Pareto distributions (GPDs) were fitted under both stationary and non‐stationary specifications. A systematic percentile‐based evaluation was performed to determine optimal exceedance thresholds, and a bootstrap‐based significance test was applied to compare stationary and non‐stationary return levels. Complementary analyses examined trends in annual frequency, mean duration, and maximum dry‐spell length. Results consistently reveal that dry‐spell behaviour across Spain is dominantly stationary. Only a very small fraction of stations show significant non‐stationary effects in the GPD location parameter, whereas non‐stationary scale, shape, or full‐parameter models provide no robust improvement and introduce substantial uncertainty. Traditional trend analyses corroborate this finding: most stations (> 70%–85%, depending on threshold) exhibit no statistically significant changes in dry‐spell frequency, mean duration, or maximum duration. Spatial patterns of change are weak, and return levels associated with long recurrence periods (e.g., 50 years) remain highly stable throughout 1961–2024. Overall, these results support long‐term stationarity in the probability of extreme dry‐spells across Spain.

Developing science-informed maps and climate service for extreme rainfall in Spain - S. M. Vicente-Serrano; S. Beguería; F. Reig; A. Royo; M. Arretxea; M. Gil; B. Latorre; A. El Kenawy; M. Franquesa; A. Halifa-Marin; M. Adell-Michavila; A. Crespillo; et al. (Natural Hazards, 2025)
This study introduces the first high-resolution hazard probability maps of extreme precipitation for Spain, marking a significant step toward a national climate service for hydrometeorological extremes. Using long-term daily precipitation records from a dense network of stations and incorporating topographic data, the methodology combines the Generalized Pareto distribution with universal kriging to spatially interpolate distribution parameters. These maps offer reliable estimates of extreme precipitation quantiles, validated against station-level observations, and are based on a stationary modelling framework—an approach supported by recent findings showing the temporal stability of such extremes in Spain and considered more robust than non-stationary alternatives. Distinct spatial patterns emerge, with intense daily precipitation distributed mainly along the Mediterranean coast and high total event precipitation in the northwest and southwest, reflecting the influence of varied weather systems. To support decision-making, the study aggregates these high-resolution data at the provincial level, aligning risk information with administrative boundaries, and enhancing its relevance for policy and planning. Furthermore, the maps are made accessible via an interactive online platform ( https://retornolluvias.csic.es ), enabling users to explore localized hazard probabilities, thereby supporting adaptation in water management and civil protection, among others.

Characteristics of widespread extreme precipitation events in Peninsular Spain and the Balearic Islands: spatio-temporal dynamics and driving mechanisms - Sergio M. Vicente-Serrano; Jose M. Garrido-Perez; José Carlos Fernández-Álvarez; Luis Gimeno-Sotelo; Santiago Beguería; Amar Halifa-Marín; Borja Latorre; Ahmed M. El Kenawy; Magí Franquesa; María Adell-Michavila; Fernando Domínguez-Castro; David Barriopedro; et al. (Climate Dynamics, 2025)
This study analysed widespread extreme precipitation events (WEPEs) across Spain using a high-density network of daily precipitation records, aiming to clarify their spatiotemporal trends and drivers. The findings reveal that WEPEs in Spain show a non-significant trend in either frequency or intensity since 1961, despite the prevailing trend of global warming. Nevertheless, atmospheric circulation plays a key role in shaping WEPEs in Spain, with five distinct synoptic patterns driving extreme precipitation across different regions. Westerly flows associated with Atlantic lows lead to widespread precipitation in northern and western Spain, while cut-off lows generate intense but more localized events, particularly in the east. Jet stream anomalies and moisture transport patterns, particularly from the Mediterranean and Atlantic, further modulate the spatial distribution and intensity of WEPEs, highlighting the interaction between regional and large-scale climatic drivers. These findings highlight the importance of distinguishing between widespread and localized EPEs and the associated atmospheric mechanisms.

An Optimal and Flexible Approach for Drought Quantification Based on Standardised Indices - Sergio M. Vicente‐Serrano; Fergus Reig; Santiago Beguería; Ahmed El‐Kenawy; Fernando Domínguez‐Castro; Magí Franquesa; Luis Gimeno‐Sotelo; María Adell‐Michavilla; Amar Halifa‐Marín; Iván Noguera; Miguel Andres‐Martin; Cesar Azorin‐Molina; et al. (International Journal of Climatology, 2025)
In this study we propose a novel approach to standardising drought indices that offers flexibility tailored to local conditions. This involves employing different probability distributions and the Akaike Information Criterion to identify the most appropriate distribution for each region and variable. Following this approach, our proposed methodology enhances the accuracy and comparability across different spatial and temporal scales, with improved representation of extreme drought events. Nonetheless, despite the increased computational requirements associated with this approach, the advantages are substantial. By enhancing accuracy, comparability and adaptability, it may improve drought monitoring and management practices. Moreover, the methodology provides a versatile framework for standardising a wide range of environmental variables beyond traditional drought indices, and software for calculations is provided ( https://github.com/lcsc/FlexDroughtIndex ). Overall, the findings of this study can advance drought assessments by providing an innovative and flexible methodology that addresses key limitations of current approaches.

Long-term vegetation dynamics in Spain’s National Park Network: insights from remote sensing data - Magí Franquesa; Maria Adell-Michavila; Sergio M. Vicente-Serrano (Environmental Monitoring and Assessment, 2025)
Understanding long-term vegetation dynamics in protected areas is crucial for assessing ecosystem resilience and informing adaptive management strategies. This study presents a comprehensive analysis of vegetation trends across Spain’s National Park Network from 1984 to 2023, using Landsat imagery processed in Google Earth Engine. Twelve national parks, representing diverse biogeographical regions and ecosystems, were analyzed using vegetation indices such as NDVI, SAVI, kNDVI, and NDMI. The Mann–Kendall test and Theil-Sen slope estimator were employed to detect monotonic trends and quantify their magnitudes, respectively. Our results reveal a predominant increase in vegetation activity across most parks over the past four decades, though with notable spatial and seasonal variations influenced by topographic gradients, bioclimatic zones, and vegetation types. High-altitude parks exhibited strong seasonal dynamics, with positive trends concentrated during the growing season, whereas Mediterranean parks showed more consistent trends throughout the year. Conversely, wetland parks like Las Tablas de Daimiel displayed concerning negative trends, highlighting ecosystem vulnerabilities associated with hydrological stress. These findings underscore the importance of integrating high-resolution remote sensing data into long-term ecological monitoring programs to track ecosystem functioning and assess management practices in protected areas. Combining remote sensing with field observations is essential to support evidence-based conservation strategies in response to climate change and other anthropogenic pressures.

Madagascar's burned area from Sentinel-2 imagery (2016–2022): Four times higher than from lower resolution sensors - V. Fernández-García; M. Franquesa; C.A. Kull (Science of The Total Environment, 2024)